The Interactive Effect of EFL Teachers’ Emotions and Cognitions on Their Pedagogical Practices - Shi, Yan (Frontiers in Psychology, 2021)
Emotion and cognition have long been considered as two influential factors determining the quality of teaching and learning. They form the foundation of all aspects of teaching as an emotional and though-provoking profession. With the advent of Positive Psychology (PP) and affective pedagogy, now EFL teachers’ inner states and emotions are placed at the center of every educational program all around the world. This consideration has led to a rise in various domains of teaching and teacher education. However, the interactive influence and association between teachers’ emotions and cognitions concerning their pedagogical practices has been mostly left ignored in EFL contexts. To fill this gap, the present study aimed to offer a mini-review of the concepts, definitions, related theories, and empirical evidence in this line of research. It also presented practical implications for different stakeholders together with research gaps and future directions for enthusiastic L2 investigators.